Can fashion entrepreneurship be feminist? Reflections from the experience of black and peripheral women from the Boa Viagem Fair (ModaPalavra e-periódico, 2025)
The article explores fashion entrepreneurship among black and peripheral women who work at Feirinha de Boa Viagem, a popular market in Recife, Brazil. The goal is to understand the perceptions, motivations and narratives of low-income women about their paths to entrepreneurship and the informal market. The debate reflects on how these dynamics are established in the light of the theory of women’s entrepreneurship and Latin American baroque economies. For the methodological approach, data was collected via in-depth interviews and subsequently analyzed through thematic analysis. A survey carried out by the municipal administration in 2018 indicated that the market comprised 178 stalls, 144 of which were operated by women. Ten female fashion entrepreneurs were interviewed. The results yielded two overarching categories, subsequently divided into: 1) motivations for engaging in entrepreneurship and 2) perceptions regarding entrepreneurship.
Keywords: women's entrepreneurship; feminist entrepreneurship; black women; baroque economies; Boa Viagem fair